The effect of magnetic field on the tunneling yield of ammonia molecules - Petrović Violeta M. (Kragujevac Journal of Science, 2021)
We analyzed the influence of magnetic component of the laser field on the tunneling yield, in a strong near-relativistic field for a squared hyperbolic secant pulse distribution. The obtained results indicate that the inclusion of the magnetic component is necessary in the observed regime.